MEMPERKENALKAN DUNIA PEMROGRAMAN: MEMBANGKITKAN MINAT SISWA/SISWI TERHADAP TEKNOLOGI DAN IT - Dhimas Galih Surya Pratama; Randy Fadhillah; Fikri Isrully Apriansyah; Doni Irawan; Bima Derian Al Bachry; Muhammad Zaky Ansharullah; Septiawan Putra (Abdi Jurnal Publikasi, 2024)
The rapid development of technology in the 21st century highlights the increasing importance of programming as a foundational skill in Information Technology (IT). Despite its significance, many students, especially at the high school level, lack awareness and interest in programming. This study focuses on introducing programming to students at SMA Muhammadiyah 25 Pamulang as a means of fostering their interest in technology and IT. By conducting workshops, interactive sessions, and practical projects, this initiative aims to make programming more accessible and enjoyable for students. The activities emphasize the relevance of programming in solving real-world problems and its role in future career opportunities. The results demonstrate a notable increase in students’ enthusiasm and understanding of programming concepts, as well as a heightened awareness of IT fields. This effort underscores the potential of early exposure to programming in nurturing a technologically literate generation ready to thrive in the digital age.